EFEKTIVITAS MACROMEDIA FLASH INTERAKTIF DALAM PEMBELAJARAN FISIKA TEKNIK - Usmeldi Usmeldi (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2012)
Technical Physics is one of supporting courses in the Technical Faculty, Padang State University (FT UNP). Preliminary survey showed that students less master the concepts of physics, making it difficult to apply in the relevant expertise courses. Therefore carried out the learning of physics with interactive media. This research aims to know the effectiveness of interactive media in improving student mastery of physics concepts. The research conducted by quasi experimental using a pretest-posttest design with control group. The research subjects were students of Electrical Engineering Education Department that follow courses of Technical Physics 2, as many as 45 people. Data were collected by using observation format, test of physics concepts mastery, and questionnaire of student responses to the implementation of learning. The research results showed that learning of physics with interactive media are effective in improving the physics concepts mastery, in terms of: (1) improved mastery of physics concepts of student was average categories, (2) the average score of physics concepts mastery of the experimental class student is higher than the control class, (3) most of the experimental class students consider that the implementation of learning of physics with interactive media was good categories. Advice submitted to the lecturer of technical physics to be able to use interactive media in the Technical Physics course. Keywords: interactive media, the mastery of physics concepts.